Management development programs and the aspired management style: a study in Malaysia - Juhdi, Nurita; Wan Jusoh, Wan Jamaliah; Supar, Norizah; Juhdi, Noor Hasni (2014)
Purpose - The study was to examine the relationship between management development programs (formal education, mentoring, on-the-job experience and assessment) and the aspired management styles (namely altruistic, goal-oriented, innovative, consultative, practical, delegating and moral-based) to be adopted by the respondents. Design/methodology/approach (mandatory) - Data was collected using survey forms that contained items that measured studied variables. The respondents were below 45 years old and performing professional occupations or in middle to higher level positions (lowest position was administrative executive). The items were adopted and adapted from Juhdi et al. (2012), Dreher and Ash (1990), Culpan and Kucukemuroglu (1993), Selvarajah and Meyer (2005) and Khaliq and Ogunsola (2011). All the items were measured on a 5-point scale, which ranged from 1 (Strongly Disagree) to 5 (Strongly Agree). Findings – 399 employees participated in the study. The findings suggested that the respondents were given “moderate” amount of support in building their managerial talents. The significant correlations indicated weak-to moderate relationships between the seven types of aspired management style and the four management development programs. Specifically, the findings indicated that only mentoring had significant relationships with all the seven aspired management styles. As for formal education, it also had significant relationships with all the aspired management styles, except for moral-based style. Assessment was found having significant relationship with consultative style with negative relationship. On-the-job experience was only significantly related to two aspired management styles (which were altruistic and delegating). Delegating style was significantly related to all the management development programs. Moral-based management style was only significant to mentoring. As for the other seven types of aspired management styles, they were significantly related to at least two management development programs. Research implications – The HR practitioners should emphasize the use of mentoring, given its consistent significant relationship with all the aspired managerial styles. Mentoring program should start with careful selection of mentors who are matched with the right protégés and must be coupled with systematic mentoring programs. Regardless of the insignificant relationships between on-the-job experience and five types of managerial styles, it should never be underestimated because it is very crucial in providing employees the skills of doing and managing business. Assessment might not be related to management style but it does contribute in giving feedbacks to employees. Research limitations – First, the correlation which ranged from .10 and .32 indicate weak-to-moderate relationships between the management programs and the aspired management styles. Second, the study only measured the first and second level of training outcomes, which are reaction and learning. It would be better if the outcomes are extended to transfer of training (which are behavior and results) which are more meaningful for evaluation.